Chapter Spazzacamini en Savoyaards - Wesseling, Lies (Amsterdam University Press, 2023)
This article engages in genealogical inquiry into Zwarte Piet (Black Pete), to gain deeper insight into the multiple semantic layers of this cultural icon. I argue that the 'roetpiet' (soot Pete) or chimney sweep is rooted in at least as solid an iconological tradition as that of the Moorish child slave. I infer some suggestions for non-offensive Sinterklaas celebrations from this historical excursion. While Zwarte Piet in his Moorish guise is indeed a flawed and racist trace of colonial slavery, his chimney sweep connotations may actually be of value to the cultural remembrance of the by now largely forgotten history of child labour that was so crucial to the early industrialization in Europe, and often still is to economies in the Global South.